Physio-morphological Indices of Seed Maturity in Aswagandha [Withania somnifera (L.) Dunal] - N. PANDIYARAJ,; PREETI,; S.K. JAIN,; KALYANI SRINIVASAN,; H.C.S. NEGI, (Seed Research, 2026)
Physiological maturity and harvesting time are the major considerations in the production of quality seeds. Experimental studies were conducted at IARI, New Delhi during late kharif of 2007-08 to identify physiological maturation and optimum duration for the harvest of the quality seeds. A minimum of 100 flowers a day were tagged, every alternate day from 0 day to 60 days from anthesis. Seed berries were harvested at periodic interval of two days starting from 02 day to 60 days, and were used for berry and other seed quality parameters. The results showed that seeds attained physiological maturity at 40-44 days from anthesis with the physio-morphological indices of maximal fresh and dry weight of seed, berry size and visual indices such as turning of berry to red colour. Seed attained germinability on 32 days from anthesis.